2009
DOI: 10.1371/journal.pgen.1000677
|View full text |Cite
|
Sign up to set email alerts
|

Life on Arginine for Mycoplasma hominis: Clues from Its Minimal Genome and Comparison with Other Human Urogenital Mycoplasmas

Abstract: Mycoplasma hominis is an opportunistic human mycoplasma. Two other pathogenic human species, M. genitalium and Ureaplasma parvum, reside within the same natural niche as M. hominis: the urogenital tract. These three species have overlapping, but distinct, pathogenic roles. They have minimal genomes and, thus, reduced metabolic capabilities characterized by distinct energy-generating pathways. Analysis of the M. hominis PG21 genome sequence revealed that it is the second smallest genome among self-replicating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
149
1
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 58 publications
3
149
1
15
Order By: Relevance
“…In urogenital human mycoplasmas, HGTs were predicted between M. hominis and the ancestor of the U. parvum/U. urealyticum group, in accordance with previous study (40). These genetic exchanges of the MIB-MIP system among mycoplasmas colonizing the same host are in complete agreement with the potential significance of this system in the evolutionary process leading to the adaptation to a new host.…”
Section: Discussionsupporting
confidence: 90%
“…In urogenital human mycoplasmas, HGTs were predicted between M. hominis and the ancestor of the U. parvum/U. urealyticum group, in accordance with previous study (40). These genetic exchanges of the MIB-MIP system among mycoplasmas colonizing the same host are in complete agreement with the potential significance of this system in the evolutionary process leading to the adaptation to a new host.…”
Section: Discussionsupporting
confidence: 90%
“…To determine whether those untypeable isolates represent new serovars or loss of markers, additional analysis such as whole-genome sequencing of such isolates would be instructive. HGT between U. parvum and M. hominis, which both localize to the mucosal surface of the human urogenital tract, was recently reported (31). Five clusters of genes encoding type I and III restriction/modification systems, transposases, and cell surface proteins were predicted to undergo HGT between the two phylogenetically distinct species.…”
Section: Discussionmentioning
confidence: 94%
“…Although mycoplasmas and ureaplasmas are characterized by their minimal genomes and are thought to have undergone regressive evolution, which usually is not favorable for active DNA acquisition (54), evidence has shown that HGT occurs among phylogenetically distinct mycoplasmal species sharing the same ecological niche (47) or within the same species (51). Comparative genomic analyses have indicated possible HGT between U. parvum and Mycoplasma hominis (31). Ureaplasma spp.…”
mentioning
confidence: 99%
“…The organism could cause pyelonephritis, pelvic inflammatory disease, postpartum and postabortion fever in addition to extragenital diseases including septicemia, joint infections, central nervous system infections, respiratory tract infections and wound infections particularly after surgery (Thomsen and Lindskov, 1979;Taylor-Robinson, 1996a;1996b;Stellrecht et al, 2004;Waites et al, 2005;Totten et al, 2008;Patel and Nyirjesy, 2010;Taylor-Robinson and Furr, 2010;Taylor-Robinson and Jensen, 2011). In newborn children, this pathogen can also can cause meningitis, pneumonia and abcess (Pereyre et al, 2009). The organism been been recovered from the upper urinary tract in patients with acute pyelonephritis (Thomsen, 1978a;1978b;Sai-Yin and Kwok-Yung, 1995), women with lower urinary tract (Humburg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%